PEMANFAATAN KEMAMPUAN MELAKSANAKAN PENELITIAN TINDAKAN KELAS/ PENELITIAN TINDAKAN SEKOLAH UNTUK MENUNJANG PROSES PENDIDIKAN DAN PEMBELAJARAN DI SEKOLAH - Herawati Susilo (Universitas Lambung Mangkurat, 2012)
The ability to carry out Classroom Action Research (CAR) or School Action Research (SAR) can be used to support the education and learning process in schools, because it make the teachers or principals as both researcher and user of research results. CAR is the research conducted by teacher in their class to improve their services to the students, entrusted to them, in developing their potency optimally by giving them the qualified learning. SAR is the the research conducted by principles in their school to improve their service to the community that gives credence by sending their son to the school. SAR will develope the profesionality of principals, teachers and all the the school staff in educational services providing. Principals may conduct SAR by encouraging teachers in inquiry process on how to make students learn, by establishing professional learning communities, through School-Based Lesson Study. Mean while, teachers may perform CAR by involving at least a friend as collaborator, by implementing CAR-based Lesson Study. Key words: CAR, SAR, Professional Development, Teachers, Principals